THE IMPACT OF ARTIFICIAL INTELLIGENCE ON THE LEGAL PROFESSION - ARKHIEREEV Nikolay Viktorovich (Правовое государство: теория и практика)
The wide spread of artificial int elligence could not but affect the legal profession, whose qualifications and professional skills are subject to new requirements under the new conditions. Purpose: to analyse the impact of artificial intelligence technology on the legal profession. Methods: empirical methods of comparison, description, interpretation; theoretical methods of formal and dialectical logic; specific scientific methods: legal-dogmatic. Results: the study allows us to conclude that a modern lawyer is not only an expert in law, but also a specialist in computer programmes, capable of posing legal questions to an artificial int elligence programme.